Considerations of Varied Thermoregulatory Expressions in Migration Theory - Clerc, Jeff; McGuire, Liam P. (Wiley, 2021)
Optimal migration theory has been used for 3 decades to generate predictions of stopover behavior and understand migration ecology. Yet, to date, there have been no attempts to understand the impacts of thermoregulation on migration theory predictions of stopover behavior. Though most migrants are homeothermic, a diverse group of migrants from bats to hummingbirds and warblers make use of some degree of heterothermy. We consider how thermoregulation influences stopover fuel deposition rates, and thus alters optimal migration theory predictions of stopover behavior using a hypothetical migratory bat as a model organism. We update the analytical models of optimal migration theory by considering scenarios of fixed metabolic rate (the current assumption of optimal migration theory) and 3 different mass-specific metabolic rates including homeothermy, shallow torpor heterothermy, and deep torpor heterothermy. Our results predict that heterotherms will make shorter stopovers, have a decreased departure fuel load, and reduce the overall time and energy costs associated with stopovers relative to homeotherms, highlighting that thermoregulation can drastically influence stopover behavior and ultimately play a critical role in population level patterns of migration.
This is the peer reviewed version of the following article: Considerations of Varied Thermoregulatory Expressions in Migration Theory, which has been published in final form at https://doi.org/10.1111/oik.08178. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.
Keywords: optimal migration theory; thermoregulation; migration ecology; torpor-assisted migration; stopover ecology